Four new species and a new name in the genus Rhyncaphytoptus Keifer(Acari: Eriophyoidea: Diptilomiopidae) from China - Song, Zi-Wei; Xue, Xiao-Feng; Hong, Xiao-Yue (Zootaxa, 2007)
Four new species in the genus Rhyncaphytoptus Keifer from China are described and illustrated, namely R. longyuwanis sp. nov. on Toxicodendron sp. (Anacardiaceae); R. tiliarium sp. nov. on Tilia sp. (Tiliaceae); R. guanegounis sp. nov. on Lonicera sp. (Caprifoliaceae); and R. yilisis sp. nov. on Betula platyphylla Suk. (Betulaceae).  A new replacement name, Rhyncaphytoputs ulmiss is provided for the junior homonym R. ulmi (Lin & Kuang) on Ulmus sp. (Ulmaceae). All species described here are vagrant on the undersurface of host leaves. A key to the species of Rhyncaphytoptus in China is provided.